Hemp-Derived Hierarchical Porous Carbon with an Optimized Pore Structure by NaOH Activation for Supercapacitor Applications - Bowornthommatadsana, Khemjiranee; Klangvijit, Kanisorn; Uwanno, Teerayut; Phonyiem Reilly, Mayuree; Yordsri, Visittapong; Chaiwat, Weerawut; Ichikawa, Satoshi; Obata, Michiko; Fujishige, Masatsugu; Takeuchi, Kenji; Wongwiriyapan, Winadda; Endo, Morinobu (My University, 2025)
This study focuses on converting hemp hurd, a byproduct of hemp stalk processing, into high-performance activated carbon for supercapacitor applications. Hemp hurd was pyrolyzed and subsequently activated with NaOH at various ratios (biochar:NaOH = 1:1, 1:2, 1:3, 1:4). The Hurd-4 condition (1:4 ratio) yielded the highest specific surface area, 3033 m2/g. Our findings indicate that increasing the chemical activation ratio enhances the mesopore-to-micropore volume ratio (Vmeso/Vmicro) to 1.58 while maintaining a sufficient micropore volume for ion storage. This balanced pore structure effectively increased the specific capacitance, achieving a maximum of 725 F/g at a current density of 0.3 A/g in a 1 M H2SO4electrolyte. When assembled into a coin cell with an organic electrolyte, Hurd-4 exhibited a maximum specific capacitance of 39 F/g, a maximum energy density of 34 Wh/kg, and a power density of 395 W/kg, surpassing commercial activated carbon. Additionally, the device maintained 78% capacitance retention after 10,000 cycles at a current density of 0.5 A/g. The superior electrochemical properties are attributed to the largest specific surface area, highest pore volume, and optimal mesopore volume ratio. These results demonstrate the potential of hemp hurd as a highly efficient precursor for synthesizing activated carbon for high-performance supercapacitors.